Paleoserological methods in examination of skeletal remains - Młodziejowski, Bronisław; Młodziejowska, Romana (Anthropological Review, 1976)
The authors have reviewed several serological methods from the viewpoint of investigators of extinct populations. There are presented methods for AB0 system examination, and to a slightly smaller extent (because of gradual extinction of activity in species-specific proteins), assesment of species characteristics from tiny bone fragments.